Plant-microbe-soil interactions in the rhizosphere: an evolutionary perspective - Lambers, Hans; Mougel, Christophe; Jaillard, Benoît; Hinsinger, Philippe (Plant and soil, 2009)
Soils are the product of the activities of plants, which supply organic matter and play a pivotal role in weathering rocks and minerals. Many plant species have a distinct ecological amplitude that shows restriction to specific soil types. In the numerous interactions between plants and soil, micro-organisms also play a key role. Here we review the existing literature on interactions between plants, microorganisms and soils, and include considerations of evolutionary time scales, where possible. Some of these interactions involve intricate systems of communication, which in the case of symbioses such as the arbuscular mycorrhizal symbiosis are several hundreds of millions years old; others involve the release of exudates from roots, and other products of rhizodeposition that are used as substrates for soil microorganisms. The possible reasons for the survival value of this loss of carbon over tens or hundreds of millions of years of evolution of higher plants are discussed, taking a cost-benefit approach. Coevolution of plants and rhizosphere microorganisms is discussed, in the light of known ecological interactions between various partners in terrestrial ecosystems. Finally, the role of higher plants, especially deep-rooted plants and associated microorganisms in the weathering of rocks and minerals, ultimately contributing to pedogenesis, is addressed. We show that rhizosphere processes in the long run are central to biogeochemical cycles, soil formation and Earth history. Major anticipated discoveries will enhance our basic understanding and allow applications of new knowledge to deal with nutrient deficiencies, pests and diseases, and the challenges of increasing global food production and agroecosystem productivity in an environmentally responsible manner.